Prevalence of type 2 diabetes is higher in peripheral artery disease than in coronary artery disease patients. (March 2015) - Silbernagel, Guenther; Rein, Philipp; Saely, Christoph H; Engelberger, Rolf P; Willenberg, Torsten; Do, Dai-Do; Kucher, Nils; Baumgartner, Iris; Drexel, Heinz
Type 2 diabetes mellitus and pre-diabetes are risk factors for atherosclerosis and are highly prevalent in patients with coronary artery disease. However, the prevalence of impaired glucose metabolism in patients with peripheral artery disease is not as well elucidated. We aimed at comparing prevalence rates of type 2 diabetes mellitus and pre-diabetes, which were diagnosed according to the current American Diabetes Association criteria, among 364 patients with peripheral artery disease, 529 patients with coronary artery disease and 383 controls. The prevalence of type 2 diabetes mellitus in peripheral artery disease patients was 49.7%. It was significantly higher in these patients than in coronary artery disease patients (34.4%; p  < 0.001) and controls (21.4%; p  < 0.001). Adjusted for sex, age and body mass index, odds ratios for type 2 diabetes mellitus were 2.0 (95% confidence interval 1.5–2.6) comparing the peripheral artery disease group with the coronary artery disease group ( p  < 0.001) and 4.0 (2.8–5.8) comparing the peripheral artery disease group with controls ( p  < 0.001). The prevalence of pre-diabetes among non-diabetic subjects was high in all three study groups (64.5% in peripheral artery disease patients, 63.4% in coronary artery disease patients and 61.8% in controls), without significant between-group differences. In conclusion, the prevalence of type 2 diabetes mellitus is even higher in peripheral artery disease patients than in coronary artery disease patients. This observation underlines the need to consider impaired glucose regulation in the management of peripheral artery disease.